Stand density and stem taper in Pinus patula Schiede et Deppe - Adlard, P; Richardson, K (Commenwealth Forestry Institute, University of Oxford, 1979)
Two studies on the effect of stand density on stem taper in even-aged plantations of Pinus patula Schiede and Deppe over short periods are reported and the need for quantifying the effect on constructing stand and tree growth models is discussed.